2018
DOI: 10.1186/s12879-018-3114-9
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity and genetic profiling of antibiotic resistance among multidrug/carbapenem-resistant Klebsiella pneumoniae isolates from a tertiary care hospital in Saudi Arabia

Abstract: BackgroundThe nexus between resistance determinants, plasmid type, and clonality appears to play a crucial role in the dissemination and survival of carbapenem-resistant Klebsiella pneumoniae (CRKP). The incidence of infections involving CRKP in Saudi Arabia is increasing and there is a need for detailed molecular profiling of this pathogen for CRKP surveillance and control.MethodsThe resistance determinants of 71 non-redundant CRKP isolates were investigated by polymerase chain reaction (PCR) and sequencing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 49 publications
5
36
3
Order By: Relevance
“…On the other hand, the current rates were even lower than the extremely high rates of cephalosporin and carbapenem resistance among GNPs reported in some developing countries such as Egypt [13], India [29], and Iran [14]. The high rate of resistance in GNPs in the current study is probably reflecting a wide range of resistance mechanisms in GNPs observed in our hospitals, such as NDM, OXA 48 and MGrb and outer membrabe protein (OMP) resistance [30][31][32][33][34]. The high rate of resistance in GNPs in the current study is quite alarming as it already increased the mortality by 25%.…”
Section: Discussioncontrasting
confidence: 66%
“…On the other hand, the current rates were even lower than the extremely high rates of cephalosporin and carbapenem resistance among GNPs reported in some developing countries such as Egypt [13], India [29], and Iran [14]. The high rate of resistance in GNPs in the current study is probably reflecting a wide range of resistance mechanisms in GNPs observed in our hospitals, such as NDM, OXA 48 and MGrb and outer membrabe protein (OMP) resistance [30][31][32][33][34]. The high rate of resistance in GNPs in the current study is quite alarming as it already increased the mortality by 25%.…”
Section: Discussioncontrasting
confidence: 66%
“…On the other hand, the current rates was even lower than the extremely high rates of cephalosporin and carbapenem resistance among GNPs reported in some developing countries such as Egypt [20], India [36], and Iran [21]. The high rate of resistance in GNPs in the current study is probably reflecting a wide range of resistance mechanisms in GNPs observed in our hospitals, such as NDM, OXA 48 and MGrb and outer membrabe protein (OMP) resistance [37][38][39][40][41]. The high rate of resistance in GNPs in the current study is quite alarming as it already increased the mortality by 25%.…”
Section: Discussioncontrasting
confidence: 65%
“…Another study done by Al-Marzooq et al [40] reported that the most common plasmid replicons were IncR and IncL/M. Moreover, a high incidence of conjugative FIIK (69%) and L/M plasmids (66%) found in CPKP isolates were reported in Saudi Arabia [41].…”
Section: Discussionmentioning
confidence: 93%